Hygiene of reproduction, maternal culture and sexual differentiation. Eugenics in Argentina and Spain during the interwar period. - Granel, Helena Andrés (Journal of Iberian & Latin American Studies, 2023)
This work analyses the ideas about maternity and female education deriving from different eugenic proposals developed in Argentina and Spain during a period of intense international debate on the implications of voluntary birth control for the future of the race and nations. In an age in which state intervention in human reproduction was presented as a solution to social healthcare problems, an enquiry is made into its evolution in these two countries where a social-hygiene approach to racial issues would prevail in different types of eugenic initiatives which, relating to diverse demographic strategies, expressed fundamental discrepancies on the permissibility or convenience of disseminating birth control methods. These different projects expressly aimed at "hygiene of reproduction" and at helping women to acquire a "maternal culture" are explored by placing the accent on the role of eugenics in the social construction of maternity. Although they took different approaches to sexual morality and bodily autonomy, they essentially propounded medical and educational ideas about reproduction which, based on the cultivation of "femininity," would establish sexual differentiation as a eugenic value to be preserved and developed in pursuit of racial improvement.